PENGEMBANGAN MEDIA CERPEN CULTURE SHOCK BERBASIS WEBSITE PADA MAHASISWA PERANTAUAN ANGKATAN 2024 PRODI BK UKSW SALATIGA - Tiorida Hutabarat; Tritjahjo Danny Soesilo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a website-based short story medium with the theme of culture shock to support the self-adjustment process of overseas students. The story presents emotional and psychological challenges commonly experienced by students when transitioning and adapting to a new cultural environment. The research employs the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) to design a digital short story that is easily accessible and relevant to the target audience. Validation by guidance and counseling experts confirmed that the media is highly feasible for use in educational and counseling services. Student evaluations showed very positive responses and supported greater understanding and self-acceptance in facing cultural transitions. This digital short story media serves as an innovative, inspiring, and practical educational alternative in character education and guidance services.